225k views
2 votes
NEED ASAP

Select the THREE expressions that are equivalent to -2(4 – 3x) + (5x – 2).

A) 2x – 10
B) 11x – 10
C) -8 + 11x – 2
D) -8 – 11x – 2
E) -8 + 6x + 5x – 2
F) -8 – 3x + 5x – 2

2 Answers

4 votes

Answer:

(B). 11x - 10 ; (C). - 8 + 11x - 2 ; (E). - 8 + 6x + 5x - 2

Explanation:

- 2(4 - 3x) + (5x - 2) = - 8 + 6x + 5x - 2 = - 8 + 11x - 2 = 11x - 10

User Sleeplessnerd
by
5.0k points
6 votes

Answer:

B , C ,E

Explanation:

Open the brackets

= -8+6x+5x-2

= -8+11x-2

= 11x-10

options. E, C and B respectively

User Siim Nelis
by
4.6k points